Prevalence and Risk Factors of Intestinal Protozoan Infections among Secondary School Students in Wukari Metropolis, Taraba State, Nigeria - Joseph T. R.; Mijah A. K.; Elizabeth A.; Ogbadu J. I; Agbakyeni H.E; Agere H.I.J. (Darul Yasin Al Sys, 2026)
Intestinal protozoan infections continue to pose public health challenges among school-aged children in developing regions, particularly where sanitation, water quality, and hygiene practices are inadequate. This study assessed the prevalence and associated risk factors of intestinal protozoan infections among secondary school students in Wukari Metropolis, Taraba State, Nigeria. A cross-sectional design was used to sample 400 students from five public secondary schools. Stool samples were examined using direct wet mount and formol-ether concentration techniques, while structured questionnaires assessed demographic characteristics, hygiene behaviour, sanitation practices, and knowledge levels. Data were analysed using descriptive statistics and chi-square tests at a 5% significance level. The overall prevalence of intestinal protozoa was 6.75% (95% CI: 4.5–9.0%), comprising Giardia lamblia (3.25%) and Entamoeba histolytica (3.50%). Maramara Government Day and Yakasaen Government Day Schools recorded the highest prevalence (10.0% each), while Government Day School had the lowest (2.5%). The difference in prevalence across schools was not statistically significant (χ² = 5.864; p = 0.661), indicating that risk factors are likely widespread across the metropolis rather than localized within specific schools. Several behavioural and environmental factors contributed to infection risk, including inconsistent handwashing before meals (38.15%), use of unsafe water sources such as streams (9.98%), and open defecation at home (19.95%) and in schools (12.22%). Knowledge gaps were substantial, as 62.84% of students were unaware of intestinal parasites, while 52.12% did not understand transmission routes. Domestic animal ownership (63.53%), irregular footwear use, and low deworming history further increased susceptibility. The findings demonstrate a moderate burden of intestinal protozoa driven by modifiable risk factors. Strengthening school-based health education, improving sanitation facilities, ensuring access to safe water, and implementing routine deworming programs are essential to reducing protozoal transmission and improving student health outcomes in Wukari Metropolis.